Navigating interstitial lung disease associated with rheumatoid arthritis (RA-ILD): from genetics to clinical landscape - Bernardinello, Nicol; Zen, Margherita; Castelli, Gioele; Cocconcelli, Elisabetta; Balestro, Elisabetta; Borie, Raphaël; Spagnolo, Paolo (Frontiers in Medicine, 2025)
Rheumatoid arthritis (RA) is a systemic autoimmune disease that affects millions of people worldwide and is characterized by persistent inflammation, pain, and joint destruction. In RA, the dysregulation of the immune system is well documented. However, the genetic basis of the disease is not fully understood, especially when extra-articular organs are involved. Interstitial lung disease (ILD) is a major cause of morbidity and mortality in patients with RA. Notably, RA-ILD shares several risk factors with idiopathic pulmonary fibrosis (IPF), namely male gender, smoking history, usual interstitial pneumonia (UIP) pattern of fibrosis, and association with the MUC5B rs35705950 polymorphism. In addition, other genetic susceptibilities are reported in RA-ILD for some HLA alleles and other less studied polymorphisms. However, the pathobiology of RA-ILD, particularly whether and to what extent genetic and environmental factors interact to determine the disease, remains elusive. In this review, we summarize and critically discuss the most recent literature on the genetics and pathogenesis of RA-ILD. The main clinical aspects of RA-ILD are also discussed.